Semantic agents for location-aware service provisioning in mobile network : master thesis = magistarski rad - Devlić, Alisa (A. Devlić ; Fakultet elektrotehnike i računarstva, 2005)
The master thesis investigates the issues of service provisioning in mobile network. Service provisioning is dened as the setting in place and conguring of the hardware and software required for activating a telecommunications service for a customer.Thethesisproposesandimplementsasolutionforaexibleandecient serviceprovisioningusingsemanticagentsinthemobilenetwork.Semanticagents areintelligentsoftwareagentsthatcollectuserpreferencesfortherequiredservice, and discover the available advertised services oered by service providers. They use the implemented matchmaking algorithm in the thesis to determine from the available services the one that best meets user's requirements. When the service is determined and found on the Web, the user can install and invoke it on the mobile device. Theservicethatwasutilizedforserviceprovisioningisthelocation-awarecontent delivery service that delivers personalized content to mobile users depending ontheircurrentlocation,utilizedterminalandpreferences.Itconsistsoftheclient andserverpart,forwhichtheprovisioningisperformedseparately.Theclientpart is provisioned on the described manner, using semantic agents. The server part of theserviceismigrated,installedandinvokedontheremotenode,usingthemultiagent system supporting remote software maintenance operations in the network. Keywords: semantic agents, location-aware services, personalized content delivery, service provisioning, semantic matchmaking